Design of microwave radiating diplexer using substrate integrated waveguide (SIW) techniques / Noor Hasimah Baba - Baba, Noor Hasimah (2019)
Recently with the demand for multi-service and multi-band modern wireless communication systems, there is a growing interest in the integration of microwave modules in RF front end systems. This thesis presents new design for the integration of microwave diplexer (two bandpass filters) and antenna using multilayer planar technology. The composite diplexer/antenna configuration in one compact module offers significant advantages especially in small physical size, low weight and ease of integration without the need to use complicated external matching networks. Two novel designs namely, substrate integrated waveguide (SIW) circular cavities diplexer (SIWCCD) and integrated SIW circular cavities diplexer with microstrip antenna (I-SIWDIPTENNA) have been successfully presented with support of theory, simulation and experimental results. The working mode for SIW circular cavity was TM010, whereas TM110 mode was chosen for the circular microstrip antenna.